Sistem Pendukung Metode Pembelajaran Self Paced Learning bagi Mahasiswa di dalam Kelas berbasis Web - Nur Azizah; Haning Galih Rani Kumbara; Probo Krishnacahya; Laura Mahendratta Tjahjono (Jurnal Pendidikan Informatika (EDUMATIC), 2023)
Currently Moodle is being used in the classroom learning process for web development courses at Universitas Ciputra by applying the self-paced learning method, but it is not optimal. Moodle features do not limit access to learning materials, so that the learning process in class is not based on actual student understanding and does not follow each student's learning pace. The purpose of this study is to determine the effectiveness of implementing self-paced learning methods in the classroom through the design of a web-based support system. This study uses a quantitative method with the SDLC model consisting of data collection, design, implementation, and system testing with Black Box. The data collection technique uses a questionnaire created with Google Form. At the design stage, the design is carried out on use case diagrams, entity relationship diagrams, and interfaces. The findings from this study are a web-based system to support students in applying self-paced learning methods in class. The test results show that all system functionality works well. This system makes the learning process in the classroom with self-paced learning more effective and helps students understand learning material well and is very effective in facilitating access to communication between students and teachers.